Normative Reasons and Moral Reasoning in the Mengzi and the Xunzi. Issue 1 (16th July 2018) - Brunozzi, Philippe
Abstract: Given that moral reasoning is directed towards providing well‐supported answers to moral questions, our understanding of what it means to be a normative reason that speaks in favor or against a line of conduct largely informs our conception of moral reasoning. This article focuses on this relationship between moral reasoning and normative reasons and tries to clarify how the early Confucian conceptions of moral reasoning we find in the Mengzi and the Xunzi are conditioned by their underlying accounts of normative reasons. This enables us to better locate and synthesize the remarks concerning moral reasoning we find in these texts.